Uptake of influenza, pneumococcal and herpes zoster vaccines among people with heart failure and atrial fibrillation. Issue 52 (12th December 2022) - Kpozehouen, Elizabeth Benedict; Tan, Timothy; Macintyre, Chandini Raina
Abstract: Background: Cardiovascular diseases are the major cause of hospitalisation and death globally. Infections exacerbate cardiovascular events among cardiac patients, contributing to all-cause mortality. Vaccination is a cheap and effective intervention that can prevent infection. In Australia, influenza, pneumococcal and herpes zoster vaccines are recommended and funded for high-risk adults such as cardiac patients. There is high prevalence of high-risk adults in Western Sydney. Objectives: This study investigates the uptake of influenza, pneumococcal and herpes zoster vaccines in patients admitted with heart failure and atrial fibrillation in a tertiary hospital in Western Sydney and factors associated with the uptake of the vaccines. Methods: Consecutive patients' hospitalised between 2014 and 2018 with heart failure or atrial fibrillation as principal diagnoses were identified. Information on patients' social demographic, clinical and vaccination status was collected and described using descriptive analysis. Univariate and multivariate analyses were conducted to determine factors associated with the uptake of the vaccines. Results: Low uptake for pneumococcal (40–45 %) and herpes zoster (15 %) vaccines were found. Prevalence of influenza vaccination was lower among participants younger than 65 (51–72 %) than in older ones (78–96 %). Australia-born participants were more likely to receive pneumococcal vaccine than those born overseas (OR 2.02, 95 % CI 1.05–3.89). Participants 65 years or older and those with comorbidities such as hypertension, COPD and chronic renal impairment were more likely to receive the vaccines. Conclusion: Multidisciplinary strategies are needed to improve access to vaccination, community knowledge, community engagement, and healthcare provider support to provide appropriate care to migrants and younger cardiac patients and reduce morbidity and mortality in this high-risk group.